Successful collection of peripheral blood stem cells upon VIDE chemomobilization in sarcoma patients - Kriegsmann, Katharina; Heilig, Christoph E.; Cremer, Martin; Novotny, Philipp; Kriegsmann, Mark; Bruckner, Thomas; Müller-Tidow, Carsten; Egerer, Gerlinde; Wuchter, Patrick (European journal of haematology, 2017)
Objectives In patients with Ewing sarcoma and some distinct subgroups of soft tissue sarcoma (STS), a quantitatively sufficient autologous peripheral blood stem cell (PBSC) collection for stem cell support might facilitate treatment continuation, dose-intensification, and high-dose chemotherapy. Here, we provide a detailed evaluation of PBSC collection upon vincristine, ifosfamide, doxorubicin, and etoposide (VIDE) chemomobilization. Methods Mobilization and collection parameters of 42 sarcoma patients (Ewing sarcoma n = 35, other STS n = 7) were analyzed retrospectively. Data were evaluated with regard to the number of previous VIDE therapy cycles. Results All patients reached the collection goal of ≥2.0 × 106 CD34+ cells/kg body weight (bw) upon VIDE/G-CSF mobilization, in the majority of cases with one single leukapheresis (LP) session (n = 29, 69%). No significant differences were identified with regard to mobilization and collection variables or the number of previous induction VIDE therapy cycles. However, upon 5 cycles of VIDE, we found the highest relative proportion of patients who required two or three LP sessions. Conclusions Our data demonstrate the feasibility of successful PBSC collection upon VIDE chemomobilization even after up to five cycles of induction therapy, while at the same time the increasing risk of bone marrow exhaustion with every consecutive cycle is outlined.
First published: 08 September 2017
Gesehen am 27.06.2018